Economic Valuation of Oceanographic Forecasting Services: A Cost-Benefit Exercise - Aline Chiabai; Paulo A.L.D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper provides an assessment of the economic value of the oceanographic services provided by the Mediterranean operational forecasting system, MFSTEP. The main purpose of this exploratory study is to carry out a cost-benefit analysis for different development scenarios, by comparing the costs associated with the project implementation with the private benefits that arise from delivering its products on the market. As far as the costs are concerned, a total cost assessment has been performed by identifying, classifying and estimating the wide range of inputs that have been allocated both to the project development and maintenance. Against this context, a cost questionnaire has been designed and administered to all MFSTEP partners. In addition, the study focuses on an end-users analysis in order to examine end-users attitudes and interests for the forecasting products, their needs and satisfaction. As before, we make the use of a survey. Finally, this questionnaire is characterized by exploring the use of the contingent valuation approach so as to address and estimate the private benefits derived from the provision of the MFSTEP products. Estimation results show that the mean willingness to pay for accessing the forecasting products amounts to 65 euro per download. Cost-benefit analysis reveals that, from a market perspective relying on the profit maximisation, a total of 163 downloads per day are required for total maintenance costs recovery, whereas 90 downloads per day are required to recover personnel maintenance costs. Finally, 33 downloads per day are required so as to recover durable equipment maintenance costs.
Keywords: D60; D61; D12; 330; Cost-Benefit Analysis; Contingent Valuation; Survey Design; Willingness to Pay; Cost Assessment; Observing and Modelling Oceanographic System; Meeresforschung; Kosten-Nutzen-Analyse; Willingness to pay; Mittelmeerraum; Umwelt-Informationssystem